Vabastamine propaganda abil. Juozas Gabrys ja Leedu iseseisvusliikumine 1911–1918 [Liberation through propaganda. Juozas Gabrys and the Lithuanian independence movement 1911–1918] - Demm, Eberhard (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2015)
During the Russian Revolution of 1905, Juozas Gabrys alias Paršaitis already played an active political role as leader of the “Farmer’s Union”and one of the three secretaries of the “Great Diet of Vilnius”. Because of Russian repression he had to emigrate to Western Europe and in 1907 settled down in Paris, where he soon established an important political network. In 1911, he founded the “Lithuanian Information Bureau” and, together with the French journalist Jean Pélissier, the “Union des Nationalités” and its journal, the “Annales des Nationalités”. His aim was to achieve independence through propaganda, not only for the Lithuanians, but also for the other oppressed nationalities in Europe. World War I offered him a great chance to realize his aim.However, as France was allied with Russia he was obliged in July 1915 to move to Lausanne in neutral Switzerland. Here he was free to organize, with only seven employees, a vast propaganda campaign to liberate Lithuania from the Russian yoke. He published three specialist periodicals but also succeeded in flooding more than 50 European newspapers with Lithuanian propaganda. He also organized several conferences the most important being the 3rd “Conference of Nationalities” on June 1916 in Lausanne, where more than 400 delegates from various nationalities denounced their oppression by Russia and Britain. He was financed by Lithuanian emigrants in America and by the German Embassy in Berne, but his greatest exploit was the world-wide collect in support of Lithuanian war victims during “Lithuanian Day” on 20 May 1917 organized by the Catholic Church, which made this “Ethnic Entrepreneur” a millionaire.His influence on political events – the creation of the “Taryba” (Lithuanian Council) and the proclamation of the independence of Lithuania as German satellite state in March 1918 – was negligible. He supported the Taryba against the oppressive German military occupation regime but neglected to create a personal power base in Lithuania, and when after the German defeat, Lithuania became genuinely independent in November 1918, he was completely excluded from the government. Last efforts in 1919 to seize power in Lithuania either with the help of a French military mission or a coups d’état failed, and thereafter the political role of Gabrys was finished.